Co‐Casting of Al and Al‐Foams. Issue 9 (31st March 2022) - Ferraris, Sara; Santostefano, Antonio; De Marco, Frediano; Campagnoli, Elena; Matteis, Paolo; Barbato, Antonio; Molina, Roberto; Ubertalli, Graziano
Abstract : The use of metal foams as permanent cores in casting products is a promising strategy. It aims to improve the properties of the cast components by adding certain foam features (e.g., lightweight, high specific stiffness, impact energy/vibration absorption ability, and good acoustic insulation properties). The use of permanent cores eliminates the steps of removal, treatment, and compulsory recycling for the traditional temporary sand cores. Herein, aluminum metals foams, in the form of bars with a dense continuous outer skin, are inserted in the die of a gravity casting experiment with an Al–Si–Cu–Mg alloy (EN AB.46400). Foams and cast objects are characterized by means of optical emission spectrometry (OES), optical microscopy (OM), scanning electron microscope equipped with energy dispersive spectroscopy (SEM‐EDS), image analysis, and computed tomography (CT). Abstract : Co‐casting of Al‐alloys and Al foams is a promising strategy for weight saving and energy absorption. Aluminum foams with a dense outer skin are used as permanent cores in gravity casting of Al‐alloy. Surface skin prevents molten metal infiltration. Proper surface preparation allows core–shell metallurgical bonding.